Notes on Recumbent Monumental Slabs incised with a peculiar form of Cross at Coldingham and elsewhere in Scotland (Proceedings of the Society of Antiquaries of Scotland, 1911)
Recumbent slabs or grave-covers, sculptured or incised with crosses of various forms, and other designs, were a common style of sepulchral monument in Scotland from the twelfth and thirteenth centuries till the period of the Reformation. Usually the plain form of incised cross has all its members rectangular in outline, but there is another form in which the extremities of the arms and summit are not rectangular, but cut off obliquely. These are the subject of the article. Several have been found in the priory of Coldingham. Wherever it is possible to fix a date for such crosses it may presumably be given as that of the sixteenth century. Other examples are known from Pluscardyn, Greenlaw, Criech, Balmerino and Tranent.